The Effect of Using Internet of Things on Improving Reading and Writing in Arabic among Seventh Grade Students in Jordan - Amal Al Oudat; Suhair Jaradat (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to reveal the impact of using Internet of Things applications in developing reading comprehension and written expression in Arabic for seventh grade students in Jordan. The study members consisted of fifty seventh grade students at Mayar International Schools affiliated to the Directorate of Education in the Capital Governorate in Jordan, during the second semester of the 2019/2020. Two sections were chosen and divided randomly into two groups, one of them was an experimental group consisting of (25) students who studied using an Internet of Things application, and the other was a control group consisting of (25) female students who studied in the usual method. To achieve the objectives of the study, an Internet of Things application, a listening skill development test, and a written expression test were prepared. The results of the study indicate that there is a statistically significant difference between the experimental and control groups in favor of the experimental group. The study recommends employing Internet of Things applications in teaching Arabic.